Setting time of construction gypsum, dental plaster, and white orthodontic gypsum - Imelda Darmawan; Octarina Willy; Johan Arief Budiman (Tabriz University of Medical Sciences, 2020)
Background. Dental plaster, white orthodontic gypsum, and construction gypsum have β-hemihydrate particles. Setting time is an essential property of dental gypsum, which can affect the strength of the material. This research aimed to compare construction gypsum, dental plaster, and white orthodontic gypsum's initial and final setting times. Methods. Three groups were included in this experimental laboratory study: construction gypsum (A), dental plaster (B), and white orthodontic gypsum (C). Each group consisted of 10 samples. Gypsum manipulation consisted of using 120 gr of powder and 60 mL of water. Gypsum powder and water were mixed using a gypsum mixer at 120 rpm. A homogeneous mixture was poured into a mold, and the setting time was measured using a Gillmore needle, according to ASTM C266-03. The initial setting time test was measured using 113.4 grams and a 2.12-mm needle. The final setting time was measured using 453.6 grams and a 1.06-mm needle. This test was repeated until the needle failed to penetrate the gypsum's surface. All the data were analyzed with one-way ANOVA and post hoc Tukey tests using SPSS 23. Results. The average initial setting time for groups A, B, and C were 10.39±1.19, 16.17±1.40, and 24.46±1.51, respectively. The average final setting time for groups A, B, and C were 15.97±0.79, 24.31±0.88) and 33.37±0.66, respectively. One-way ANOVA and post hoc Tukey tests showed significant differences in the initial and final setting times between the three groups (P<0.05). Conclusion. There were differences in setting time between dental plaster, white orthodontic gypsum, and construction gypsum. The construction gypsum's setting time is suitable as a type II dental gypsum, according to ADA No.25.